Survey of the Undergraduate Health Status during the Outbreak of COVID-19: a Case Study of an Urban University in Thailand: Undergraduate Health Status during COVID-19 - Jirathananuwat, Areeya; Woratanarat, Thira; Papukdee, Pramote (Vajira Medical Journal : Journal of Urban Medicine, 2023)
OBJECTIVE: This study aimed to survey the health status of undergraduates during the outbreak of COVID-19 in Thailand. METHODS: This cross-sectional descriptive study recruited undergraduate students from a university in an urban area in Thailand. The survey was conducted online by the electronic mailing of questionnaires to the studied participants. The daily health behaviors questionnaire, the 28-item General Health Questionnaire (Thai GHQ28), and the participants’ satisfaction with the online learning questionnaire were used in this study. RESULTS: There was a total of 390 undergraduate students who participated and responded to the survey. The results showed they scored poorly in the areas of controlling food consumption, such as salt and sweet intakes, and exercise or continuous movement. The majority of the surveyed students (303 out of 390 students or 77.7% of the total) have shown a normal health status in response to the Thai GHQ28 except for social dysfunction. There was a strong association between daily health behaviors (p = 0.015) and general health (p = 0.019) status with the online satisfactory level. CONCLUSION: At-home online learning was found to be directly associated with the health behaviors and the health status of the surveyed students. Based on the findings, counseling centers should be set up to offer advice to students on how to stay healthy and socially connected during the online learning period.